Power and cinematic conditions of the exhaust mechanism of foundry installation for hollow castings cast by freezing process - V. F. Bevza; A. M. Bodiako; V. S. Mazko (Литьë и металлургия)
Is determined an optimal composition of a high content Br alloy with good technological and mechanical characteristics for its use in casting production.